Beyond Average: Providers' Assessments of Indices for Measuring Pain Intensity in Patients With Chronic Pain - Goldman, Roberta E.; Broderick, Joan E.; Junghaenel, Doerte U.; Bolton, Alicia; May, Marcella; Schneider, Stefan; Stone, Arthur A. (Frontiers in Pain Research, 2021)
Introduction. Effective clinical care for chronic pain requires accurate, comprehensive, meaningful pain assessment. This study investigated healthcare providers’ perspectives on seven pain measurement indices for capturing pain intensity. Methods. Semi-structured telephone interviews were conducted with a purposeful sample from four US regions of 20 healthcare providers who treat patients with chronic pain. The qualitative interview guide included open-ended questions to address perspectives on pain measurement, and included quantitative ratings of the importance of seven indices [average pain, worst pain, least pain, time in no/low pain, time in high pain, fluctuating pain, unpredictable pain]. Qualitative interview data were read, coded and analyzed for themes and final interpretation. Standard quantitative methods were used to analyze index importance ratings. Results. Despite concerns regarding 10-point visual analog and numeric rating scales, almost all providers used them. Providers most commonly asked about average pain, although they expressed misgivings about patient reporting and the index’s informational value. Some supplemented average with worst and least pain, and most believed pain intensity is best understood within the context of patient functioning. Worst pain received the highest mean importance rating (7.60), average pain the second lowest rating (5.65) and unpredictable pain the lowest rating (5.20). Discussion. Assessing average pain intensity obviates obtaining clinical insight into daily contextual factors relating to pain and functioning. Pain index use, together with timing, functionality and disability, may be most effective for understanding the meaning to patients of high pain, how pain affects their life, how life affects their pain, and how pain changes and responds to treatment.